Control of 3x7 matrix converter with PWM three intervals modulation - Mesai, H; Bentaallah, A; Djeriri, Y; Mahmoudi, A (جامعة الوادي - university of el oued, 2019)
Direct Power conversion from fixed AC voltage into variable AC voltage is gaining a significant attention, especially in case of multi-phases machines/generators; for such reason a new algorithm to control 3x7 matrix converter (MC) is developed in this paper, wherein the main aim is to control multi-phases induction motor/generator connected to the electrical grid with a novel converter (except matrix converter), for that the PWM three intervals modulation strategy is modified from the control of 3x3 MC to 3x7 MC; which is directly connected to the network through a three phase input in order to overcome the supplying problems, on the other side seven phases have been used as an output to benefit the advantages of the multi-phases machines. This paper intends in the first place to explain the 3x3 MC, then to manipulate the control equation for the purpose of making it suitable for controlling the 3x7 MC effectively, thus a good performance can be clearly seen according to the quality of the output voltage/current under typical R-L load, the shift between phases and the THD evaluation. The obtained simulation results which demonstrate the efficiency of the new control algorithm are presented and discussed
Article
Keywords: 3x3 Matrix converter, 3x7 Matrix converter, PWM three intervals, R-L load, THD